2013
DOI: 10.3390/ma6125893
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Nanostructures in Organogels Based on a Bolaform Cholesteryl Imide Compound with Conjugated Aromatic Spacer

Abstract: The self-assembly of small functional molecules into supramolecular structures is a powerful approach toward the development of new nanoscale materials and devices. As a class of self-assembled materials, low weight molecular organic gelators, organized in special nanoarchitectures through specific non-covalent interactions, has become one of the hot topics in soft matter research due to their scientific values and many potential applications. Here, a bolaform cholesteryl imide compound with conjugated aromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…We compared the NH‐ stretching frequencies of sample from 1:1 MeOH/CHCl 3 , with the initial powder form of the sample (blue line in Figure c). The presence of broad NH‐bands in the former indicated the presence of hydrogen bonds (Table S2) . We believe that these hydrogen bonds facilitate vesicular assembly.…”
Section: Study Of Self–assemblymentioning
confidence: 90%
“…We compared the NH‐ stretching frequencies of sample from 1:1 MeOH/CHCl 3 , with the initial powder form of the sample (blue line in Figure c). The presence of broad NH‐bands in the former indicated the presence of hydrogen bonds (Table S2) . We believe that these hydrogen bonds facilitate vesicular assembly.…”
Section: Study Of Self–assemblymentioning
confidence: 90%
“…In addition, we have characterized the gelation behaviors of some bolaform cholesteryl amide compounds with large conjugated spacer [43,44]. We found that the formed nanostructures and self-assembly process in organogels could be regulated by solvent change.…”
Section: Advances In Colloid Sciencementioning
confidence: 97%
“…Moreover, for CH-C2 and CH-N1, the inefficient or poor gelation behaviors in used solvents may be mainly attributed to the too rigid or too flexible spacers in molecular skeletons, which cannot cause enough intermolecular forces to Moreover, another bolaform cholesteryl imide derivative with conjugated aromatic spacer was designed and prepared. The gelation performances in 23 solvents were tested as efficient lowmolecular-mass organic gelator [64]. The obtained data demonstrated that the morphologies and assembly modes of as-prepared organogels can be changed by regulating different kinds of organic solvents.…”
Section: Preparation and Self-assembly Of Supramolecular Gels Based Omentioning
confidence: 99%